Statute of limitations for a dividend claim in capital companies - Moniczewski, Karol (Studia Iuridica Toruniensia, 2023)
The article presents a cross-sectional analysis of the claim for dividend payment in capital companies. It discusses the emergence of the obligation to pay dividends, the maturity of the claim and the statute of limitations. In the course of the analysis an attempt was made to create a coherent conception of the emergence of a legal relationship concerning the payment of dividends. The article defends the thesis that dividend payment is a one-time benefit, and the claim for dividend payment is time-barred on general principles. The study is based on the dogmatic-legal method, analyzing the provisions of the Code of Commercial Companies and the Civil Code, taking into account the literature on the subject and the case law of the Supreme Court.